Blow-up to a $p$-Laplacian parabolic equation with a general nonlinear source - Ding, Hang; Zhou, Jun (Comptes Rendus. Mécanique)
A $p$-Laplacian parabolic equation with a general nonlinear source term is considered. It is shown that the solution may blow up in finite time at positive initial energy. Moreover, under some suitable assumptions about the nonlinear source term, the solution is proved to blow up in finite time at arbitrarily high initial energy. These results generalize the previous ones.